2016
DOI: 10.1038/srep37530
|View full text |Cite
|
Sign up to set email alerts
|

Inverse changes in L1 retrotransposons between blood and brain in major depressive disorder

Abstract: Long interspersed nuclear element-1 (LINE-1 or L1) is a type of retrotransposons comprising 17% of the human and mouse genome, and has been found to be associated with several types of neurological disorders. Previous post-mortem brain studies reveal increased L1 copy number in the prefrontal cortex from schizophrenia patients. However, whether L1 retrotransposition occurs similarly in major depressive disorder (MDD) is unknown. Here, L1 copy number was measured by quantitative PCR analysis in peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…Here, we consider association as a study having shown that a retrotransposon insertion, or insertions, may cause a disease, or the study having reported elevation of retrotransposon copy number or mRNA level in the brain tissue of affected individuals when compared with healthy individuals. retrotransposon neurological disease insertions activity (mRNA levels, CNV, biomarkers) HERV multiple sclerosis [ 166 168 ] 3q13.31 microdeletion syndrome [ 169 ] amyotrophic lateral sclerosis [ 170 , 171 ] multiple sclerosis [ 166 168 , 172 ] schizophrenia [ 173 176 ] bipolar disorder [ 173 , 175 , 177 ] HIV-associated dementia [ 178 ] major depression [ 177 ] autism [ 179 ] ADHD [ 180 ] L1 pyruvate dehydrogenase complex deficiency [ 110 ] Fukuyama-type congenital muscular dystrophy [ 181 ] neurofibromatosis type I [ 182 ] ataxia with oculomotor apraxia 2 [ 183 ] glioblastoma [ 184 , 185 ] schizophrenia [ 176 ] ataxia telangiectasia [ 54 ] Coffin Lowry syndrome [ 186 ] major depression [ 187 , 188 ] schizophrenia [ 187 189 ] Rett syndrome [ …”
Section: Retrotransposition In Neurological Diseasementioning
confidence: 99%
“…Here, we consider association as a study having shown that a retrotransposon insertion, or insertions, may cause a disease, or the study having reported elevation of retrotransposon copy number or mRNA level in the brain tissue of affected individuals when compared with healthy individuals. retrotransposon neurological disease insertions activity (mRNA levels, CNV, biomarkers) HERV multiple sclerosis [ 166 168 ] 3q13.31 microdeletion syndrome [ 169 ] amyotrophic lateral sclerosis [ 170 , 171 ] multiple sclerosis [ 166 168 , 172 ] schizophrenia [ 173 176 ] bipolar disorder [ 173 , 175 , 177 ] HIV-associated dementia [ 178 ] major depression [ 177 ] autism [ 179 ] ADHD [ 180 ] L1 pyruvate dehydrogenase complex deficiency [ 110 ] Fukuyama-type congenital muscular dystrophy [ 181 ] neurofibromatosis type I [ 182 ] ataxia with oculomotor apraxia 2 [ 183 ] glioblastoma [ 184 , 185 ] schizophrenia [ 176 ] ataxia telangiectasia [ 54 ] Coffin Lowry syndrome [ 186 ] major depression [ 187 , 188 ] schizophrenia [ 187 189 ] Rett syndrome [ …”
Section: Retrotransposition In Neurological Diseasementioning
confidence: 99%
“…Growing evidence suggests that the roles of retrotransposable elements underlie progression of multiple neuronal diseases [ 15 , 16 ]. Here, we report that the caudate genome of the Huntington’s disease mouse model exhibits increased copies of L1 retrotransposon and are associated with the increased transcription of its transcripts, ORF1 and ORF2.…”
Section: Discussionmentioning
confidence: 99%
“…The L1 content was evaluated as copy number content of ORF1 and ORF2 in brain and liver tissues samples of both HD transgenic and control mice. The method used to determine the L1 content was followed as described previously with minor modifications [ 15 , 19 ]. Briefly, 500 pg of DNA was used as a template and was amplified using m5′UTR-, mORF1-, and mORF2-specific primer sets in an SYBR green assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other observations have confirmed the expression of transposons in the brains of healthy and stressed rodents, primates, and humans under normal conditions. Changes in their expression occur in many disorders of the nervous system, including amyotrophic lateral sclerosis, depression, and schizophrenia (108)(109)(110)(111)(112)(113)(114). Thus, the importance of these elements to understand complex disorders such as PTSD is apparent (115,116).…”
Section: Retrotransposonsmentioning
confidence: 99%